CSDSim: A didactic processor simulation environment based on the client / server architecture - Rodrigues, Gustavo R.; Becker, Douglas M.; Wagner, Flávio R. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41227, 2000)
Computer processors are incredibly complex and many times hard to evaluate and understand. Moreover, processor organization can hardly be studied on a pure theoretical base, and experimenting with real processors does not allow the analysis of the internal processor structure. Therefore, the use of simulation models that describe their behavior can facilitate their comprehension. This work introduces CSDSim, a didactic environment for teaching and evaluating processor organizations using the DLX processor. The environment is based on a client / server architecture and uses concepts of Visual Interactive Simulation and Object Oriented Hardware Modeling.